Educação Física no Exame Nacional do Ensino Médio: análise via teoria clássica dos testes / Educación física en el Examen Nacional de la Secundaria Superior: análisis por la teoría clásica de las pruebas - Araujo de Sousa, Leandro; de Freiras Pontes Junior, José Airton; Eufrásio Braga, Adriana (Universidad de Costa Rica, 2020)
The National Exam of Upper Secondary Education (ENEM) in Brazil, is a large scale evaluation that aims to measure students' knowledge at the end of Basic Education. Physical Education began to form of the Exam in 2009. Thus, the research aimed to analyze the Physical Education items of the exam from the years 2009 to 2014 from the classical theory. The research has a predominantly quantitative and exploratory approach. The study was performed with a random sample of participants from state of Ceará, Brazil, who were examined. The following parameters were analyzed: validity, reliability, difficulty and discrimination. The items presented good values ​​of correlation and adequacy of the sample. However, they presented commonality scores and factorial loads that were not adequate for the test composition. The Exploratory Factor Analysis presented low explanation of the variance considering only one factor, even Scree plot indicating the unidimensionality. The reliability values ​​were good, with no influence of Physical Education items. The difficulty and discrimination presented values ​​acceptable in almost every year. However, the test did not present unidimensionality in 2014. This year, the items presented high difficulty and low discrimination. Thus, some Physical Education items of the exam did not present adequate parameters. The tests of Languages ​​and Codes presented difficulties in proving unidimensionality. Such factors may compromise the validity of the measure and consequently of the results of this exam, and may interfere with the enrollment of millions of Brazilians in Higher Education.